Manajemen Kepala Sekolah Dalam Mengembangkan Budaya Agama di MTs Muhammadiyah 22 Padangsidimpuan - Nita Rahayu; Darliana Sormin; Rosmaimuna Siregar (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
In order to understand aspects of principal management planning in developing religious culture, which has become a habit or obligation, the researcher raised the title principal management in developing religious culture at SMP Negeri 1 Padangsidimpuan. This type of research is qualitative research. The techniques and sources used are observation, interviews and documentation to obtain the required data. After conducting research and discussion, the conclusion was obtained: As a school principal, you should be able to provide an example of discipline and the Islamic religion applied every day in carrying out congregational prayers and memorizing short surahs and short lectures to students, so that each leader can be a role model for his subordinates. The managerial skills of the school principal must be improved in order to create new ideas to develop the school even more than before, so that a teacher can improve the quality of children to become good graduates, to be qualified and competent.